Personal development counseling through superior cognitive with modeling Vasudeva Krishna and glorious Bhisma - Dharsana, I Ketut (Department of Guidance and Counseling, FIP, Undiksha, 2017)
This research aims to know the influence of philosophical values of cognitive counseling theory with engineering modeling modeling techniques and Vasudeva Krishna Noble Bhisma to develop personally excelled in personal development courses Counselors through lesson study on student semester IV Department of BK FIP Undiksha. This type of research was quasi experimental research. The number of students of the subject is 33 students consisting of 19 women and 14 men. The source of the data in this study is the result of observations, interviews, results of filling diaries, and the results of questionnaires filling. Superior personal data collected with the test results. Methods of analysis used is the test of the t-test. The results showed that there is the influence of cognitive counseling with techniques of Vasudeva Krishna and modeling techniques that glorious modeling Bhisma against superior personal development through lesson study.